Incarcerated Fatherhood: the Entanglements of Child Support Debt and Mass Imprisonment - Haney, Lynne A. (The American journal of sociology, 2018)
With evidence comprising three years of ethnographic research in child support courts and 125 in-depth interviews with formerly incarcerated fathers, the author shows how criminal justice and child support provisions work in tandem to create complicated entanglements for fathers. She develops the concept of incarcerated fatherhood—a matrix of laws, policies, and institutional practices that shape formerly incarcerated men’s relationship to parenting. On the one hand, she analyzes the debt of imprisonment, or the material costs of paternal incarceration; on the other, she examines the imprisonment of debt, or the punitive costs of child support debt. She then brings these two entanglements together to analyze their effects on men’s lives as fathers. Instead of “piling up” in men’s lives, these entanglements work in circular ways to form feedback loops of disadvantage that create serious obstacles for men as parents and complicate precisely those relationships proven essential for reintegration after prison: familial relations of care, reciprocity, and interdependence.